Tecnologia, ??tica e cidadania nas percep????es de professores da UAB - Medeiros, Cid (2017)
This exploratory project research aims to contribute to teacher education curriculum discussions as far as ethics and citizenship within cyberculture are concerned. It's purposes are to describe the teacher's socio-demographic profile, their perception regarding the Information and Communication Technologies (ICT) applications as well as the possible relation between their ethical perception and the selected courses Political-Pedagogical Projects (PPP'S). On the quantitative side, a survey was applied to the teachers in order to outline, on the basis of their use and behaviors perspective, the ethical-citizen perceptions associated to the applications of those technologies. On the qualitative side, PPP'S were investigated by means of content analysis. The theoretical framework applied to the research is regarding those main categories developed in The Human Condition by Hannah Arendt. The results describe the sample as teachers with 40 years of age in average, followed by 12 years of schooling experience composed for the most part by females (62%) living in the South and Southeast Brazilian countryside. Their perceptions suggest positive perception towards alterity and low quality of information shared online, but moderately weak critical thinking in relation to privacy civil right, followed by inhibited political participation and lack of convergence between curricular projects and the teacher's effective perceptions.